Dynamic Prudential Regulation - Subramanian, Ajay; Yang, Baozhong (Management Science, 2020)
We analyze the design and impact of bank regulation using a dynamic structural framework. The optimal regulatory policy combines a target capital requirement, the mitigation of underinvestment, an intervention capital requirement to control inefficient risk taking, and recapitalization of distressed banks. The optimal target and intervention capital requirements from our structural estimation are consistent with the substantially higher capital requirements proposed in Basel III and together achieve most of the regulatory benefits by alleviating underinvestment and asset substitution. They are interdependent and respond differently to banks’ asset characteristics, thereby suggesting that regulatory policies should be carefully tuned to the economic environment. This paper was accepted by Kay Giesecke, finance.